Konsep Kesetaraan Gender Perspektif Fatima Mernissi - Andri Sutrisno; Dini Salsabela (UIN Mataram, 2022)
Fatima Mernissi is a figure of modern Muslim feminism. Gender issues and women's issues are always interesting to study. Although women play a role in social, economic and other positions, they are still under a smaller portion than men. Women are often considered to have no abilities, in contrast to men who are considered capable of holding power in all fields. This research uses a qualitative descript approach with the type of library research. Meanwhile, the data collection technique uses libraries and data analysis uses data reduction, data exposure and conclusions. So that in this study we get the following findings: 1. That fatima mernissi is a female figure from Maroka who has a mission about the importance of gender equality in modern life. 2. That gender equality according to fatima mernissi is a study that demands gender equality between men and women because it is influenced by culture, human rights and religious pluralism.